Plasma fatty acid lipidome is associated with cirrhosis prognosis and graft damage in liver transplantation. Issue 2 (25th June 2014) - Ginanni Corradini, Stefano; Zerbinati, Chiara; Maldarelli, Federica; Palmaccio, Giuseppina; Parlati, Lucia; Bottaccioli, Anna Giulia; Molinaro, Antonio; Poli, Edoardo; Boaz, Mona; Serviddio, Gaetano; Mennini, Gianluca; Corsi, Alessandro; et al.
ABSTRACT: Background: Knowledge regarding the plasma fatty acid (FA) pattern in patients with liver cirrhosis is fragmentary. Objective: We evaluated plasma FA lipidome and its association with the prognosis of cirrhosis and severity of liver graft damage after transplantation. Design: In this observational study, plasma FA lipidome was investigated in 51 cirrhotic patients before liver transplantation and in 90 age- and sex-matched healthy control subjects. In addition, we studied ischemia-reperfusion damage in the liver of 38 patients for whom a graft biopsy was available at transplantation. With the use of logistic regression, we modeled the presence of cirrhosis, the dichotomized model for end-stage liver disease score below and above the median, and the presence of severe liver graft ischemia-reperfusion damage. Results: The FA pattern was markedly altered in cirrhotic patients, who showed, compared with healthy controls, higher monounsaturated FAs, lower n-6 and n-3 polyunsaturated FAs, and undetectable cerotic acid. Plasma di-homo-γ-linolenic acid was independently associated with the presence of cirrhosis (OR: 0.026; 95% CI: 0.004, 0.196; P < 0.0001), severity of its prognosis (OR: 0.041; 95% CI:0.005, 0.376; P = 0.006), postreperfusion graft hepatocellular necrosis (OR: 0.921; 95% CI: 0.851, 0.997; P = 0.043), and sinusoidal congestion (OR: 0.954; 95% CI: 0.912, 0.998; P = 0.039). Associations of di-homo-γ-linolenic acid with the presence of cirrhosis and severity of its prognosis were confirmed also after false discovery rate correction. Conclusions: Cerotic and di-homo-γ-linolenic acids may serve as markers of disease and prognosis in liver cirrhosis. Dietary supplementation with di-homo-γ-linolenic acid could be a reasonable interventional strategy to delay disease progression in liver cirrhosis. This trial was registered at clinicaltrials.gov as NCT01389115.